THE EFFECT OF GAMES AND TRAINING PROGRAMS OFFERED AT BALL SCHOOL (BALSCHULE), ON BALL-COORDINATION AMONG FIRST AND SECOND GRADE STUDENTS - Behrooz Ebrahimi (Kharkov National Pedagogical University, 2013)
The aim of this study is to investigate the effect of games and training programs offered at the Ball school (Ballschule Heidelberg), on ball-coordination among first and second grade students. For this purpose, 38 students from 13 schools covered by the Ball school (Heidelberg Balschule), were chosen as the experimental group (non-random) ; in the meantime the consent of the students' parents were also received. Forty students as well as a control group (non-random) of eight normal schools were selected with parental consents. Then through using ball-coordination tests [BKT (BallKoordinationstests). Ball Coordination's Tests], the level of the ball skills among both groups were measured in the pre-test and Post-test. Tests included kicking ball against the wall (under five conditions). The research methods were semi-experimental with experimental and control groups. Independent variables were also applied to the experimental group and the means and standard deviations were calculated through descriptive statistics. And then, a T-test for statistical analysis of data in related groups were applied. The results showed a significant effect of games and training programs offered at the school ball in the ball-coordination of subjects.